2020
DOI: 10.3386/w26662
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Consequences of Being Denied an Abortion

Abstract: Restrictions on abortion are pervasive, yet relatively little is known about the financial and economic impact of being denied an abortion on pregnant women who seek one. This paper evaluates the economic consequences of being denied an abortion on the basis of the gestational age of the pregnancy. Our analysis relies on new linkages to administrative credit report data for participants in the Turnaway Study, the first study to collect high-quality, longitudinal data on women receiving or being denied a wanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 62 publications
1
38
0
Order By: Relevance
“…In addition, the same study found that those denied an abortion had a higher rate of life‐threatening physical health risks than those who obtained abortions 34 . Finally, an economic analysis of the Turnaway Study population found that when compared with those who were able to obtain an abortion, those denied abortions had increased markers of financial distress, including higher unpaid past‐due debts, more evictions and bankruptcies, and lower credit scores 35 . These data are consistent with the self‐reported experiences of patients seeking abortion in Texas after clinic closures in that state: Gerdts and colleagues reported that clinic closures were associated with higher out‐of‐pocket costs for patients, more frustrated requests for medication abortion and an increase in the reported difficulty of accessing abortion 7 .…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the same study found that those denied an abortion had a higher rate of life‐threatening physical health risks than those who obtained abortions 34 . Finally, an economic analysis of the Turnaway Study population found that when compared with those who were able to obtain an abortion, those denied abortions had increased markers of financial distress, including higher unpaid past‐due debts, more evictions and bankruptcies, and lower credit scores 35 . These data are consistent with the self‐reported experiences of patients seeking abortion in Texas after clinic closures in that state: Gerdts and colleagues reported that clinic closures were associated with higher out‐of‐pocket costs for patients, more frustrated requests for medication abortion and an increase in the reported difficulty of accessing abortion 7 .…”
Section: Discussionmentioning
confidence: 93%
“…17 Short-term barriers to accessing abortion during the current pandemic are likely to have long-term negative effects. Longitudinal research among U.S. women who were unable to obtain wanted abortions found that, compared with individuals who had terminated a pregnancy, those who had been denied an abortion and forced to carry to term experienced more debt, had lower credit scores 18 and were more likely to have poverty-level incomes four or more years later. 19 They also experienced more chronic pain, had worse self-reported health 20 and were more likely to experience sustained physical violence from the man involved in the pregnancy.…”
Section: Potential Consequences For Individualsmentioning
confidence: 99%
“…Examining barriers to abortion care is important, as denying women* desired abortions may be associated with poorer maternal bonding, lower child development scores and greater economic insecurity. [1][2][3][4][5] Women who are denied a wanted abortion may experience more partner violence, 6 more anxiety, lower self-esteem, and less life satisfaction, 7,8 and have less aspirational life plans 9 compared to those who are successful in having a wanted abortion. Unintended pregnancies are associated with greater odds of having a low birth weight baby, and stillbirth or neonatal death may be more common.…”
Section: Introductionmentioning
confidence: 99%